Insights Into Ferroptosis, a Novel Target for the Therapy of Cancer - Wang, Hong-Tao; Ju, Jie; Wang, Shao-Cong; Zhang, Yu-Hui; Liu, Cui-Yun; Wang, Tao; Yu, Xue; Wang, Fei; Cheng, Xue-Ru; Wang, Kun; Chen, Zhao-Yang (Frontiers in Oncology, 2022)
Ferroptosis is a new form of programmed cell death (PCD) characterized by an excess iron accumulation and subsequent unbalanced redox states. Ferroptosis is different from the already reported PCD and has unique morphological features and biochemical processes. Ferroptosis was first elaborated by Brent R. Stockwell’s lab in 2012, in which small molecules erastin and RSL-3 induce PCD in Ras mutant cell lines. Ferroptosis involves various physiological processes and occurrence of disease and especially shows strong potential in cancer treatment. Development of small molecule compounds based on Stockwell’s research was found to kill cancer cells, and some FDA-approved drugs were discovered to result in ferroptosis of cancer cells. Radiotherapy and checkpoint therapy have been widely used as a treatment for many types of cancer. Recently, some papers have reported that chemotherapy, radiotherapy, and checkpoint therapy induce ferroptosis of cancer cells, which provides new strategies for cancer treatment. Nevertheless, the limitless proliferation of tumor cells and the lack of cell death mechanisms are important reasons for drug resistance for tumor therapy. Therefore, we reviewed the molecular mechanism of ferroptosis and sensitivity to ferroptosis of different cancer cells and tumor treatment strategy.